Can Intracapsular Tonsillectomy Be an Alternative to Classical Tonsillectomy? A Meta‐analysis. (18th April 2017) - Kim, Jong Seung; Kwon, Sam Hyun; Lee, Eun Jung; Yoon, Yong Joo
Abstract : Objective: Tonsillectomy is the most common operation performed in the otolaryngologic fields. Efforts have been made to reduce postoperative complications, and one of these is intracapsular tonsillectomy and adenoidectomy (ICTA), which leaves the tonsillar tissue with tonsillar capsule. This study aimed to evaluate intracapsular tonsillectomy compared with classical extracapsular tonsillectomy in terms of efficacy of the technique for managing obstructive sleep apnea (OSA) and reducing postoperative complications. Data Sources: We performed a literature search using PubMed, EMBASE, and the Cochrane Library through December 2016. Review Methods: Summarized risk ratio (RR), risk differences (RDs), and standardized mean differences (SMDs) with 95% confidence intervals (CIs) were estimated by summarizing the risk estimates of each study using random‐effects models that considered both within‐ and between‐study variations. Results: Our search included 15 randomized controlled studies. The RRs for postoperative bleeding and residual tonsils were, respectively, 0.44 ( P =. 01) and 6.02 ( P =. 0002). There were significant differences in postoperative pain ( P =. 0022), need for analgesics ( P <. 0001), days to normal diet ( P =. 006), and days to normal activity ( P <. 00001) between intracapsular tonsillectomy and extracapsular tonsillectomy. Conclusions: Intracapsular tonsillectomy can effectively reduce postoperative pain and bleeding, which shortens the time required to return to normal life. There was no difference between microdebrider and coblator in intracapsular tonsillectomy regarding postoperative pain and bleeding. It can increase the risk of remnant tonsils; however, it does not increase the risk of recurrent infection.